Future stories : what's next? - Christian, David, 1946- (Little, Brown Spark, 2022)
"The future is uncertain, a bit spooky, possibly dangerous, maybe wonderful. We cope with this never-ending uncertainty by telling stories about the future, future stories. How do we construct those stories? Where is the future, the place where we set those stories? Can we trust our future stories? And what sort of futures do they show us? This book is about future stories and future thinking, about how we prepare for the future. Think of it as a sort of User's Guide to the Future. We all need such a guide because the future is where we will spend the rest of our lives."--